The efficacy of structured assessment and analgesia provision in the paediatric emergency department. Issue 1 (20th December 2004) - Boyd, R J; Stuart, P
Abstract : Objectives: To ascertain if the use of a structured pain assessment tool and nurse initiated oral analgesia protocols improve uptake and time to analgesia for children presenting to the emergency department with minor or moderate musculoskeletal injuries. Methods: Three groups of children with peripheral limb injuries were examined to identify the rates of analgesia provision and time from attendance to analgesia provision. These groups corresponded to an initial group with no pain scoring and physician initiated analgesia, a second group with pain scoring at triage then physician initiated analgesia, and a third group with pain scoring and nurse initiated analgesia. Results: The mean time to analgesia in the initial group was 138 minutes. After initiation of triage pain assessment the mean time to analgesia was 93 minutes, there was no statistical difference between these two groups. After the introduction of nurse initiated analgesia, the time to analgesia fell to a mean of 46 minutes. The rate of analgesia provision was initially 20.5% while after the initiation of triage pain assessment the provision rate was 23%. After the initiation of nurse initiated analgesia the analgesia provision rate significantly rose to 34% of attendances. Conclusions: The use of a nurse initiated, oral analgesia protocol for treatment of children with mild to moderate injury can significantly increase analgesia provision rates and decrease time to provision of analgesia.